Investasi Tanaman Kayu Sengon dalam Wanatani Cukup Menjanjikan - Sri - Hardiatmi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2010)
ABSTRACT Lodging business is a promising alternative of investation more over if the lodging commodity has the highly economy value. Planting lodge is much simpler comparing to planting another agricultural which need more intensive cultivation. For the farmer, as long as his area is possible to be used to grow sengon lodge, this business is very important for future saving. The reason is because sengon lodge can be harvested any time not depend on the season. Another reason is that the lodging commodity price it self is never decrease and keep increasing every year. The needs of sengon lodging commodity, either for domestic or export never stop along with the human life it self more over the number of lodging productivity which come from natural forest is decreasing lately. Key words : Agroforestry, Sengon lodging business.